Antecedents and consequences of consumer ethnocentrism in an emerging market: uncovering implicit attitudes using the implicit association test - Till, Darren Stewart (My University, 2022)
With an increase in globalization, and a simultaneous decline in industry growth, South African brand managers in the fast-moving consumer goods (FMCG) sector need to consider appropriate marketing strategies to remain competitive against the ever-encroaching multinational conglomerates. Fortunately, international marketing may have a solution in the form of consumer ethnocentrism – a socio-psychological trait that manifests as a general preference for local products, as opposed to those imported. Despite a distinct dearth of research in Africa, the predominant consensus within the field is that consumer ethnocentric tendencies (CET) are linked to a nation’s economic prosperity, and that consumers in developing countries generally prefer foreign products. However, research has begun to emerge which brings the validity of such an assumption into question. It is on this premise that the current research enquiry attempts to address the inconsistencies of the extant body of research, which has primarily operationalized traditional market research techniques that are fraught with response biases and other methodological shortfalls. Thus, by employing a combination of implicit (non-direct) and explicit (self-report) survey techniques this study attempts to uncover consumers’ true, nonconscious attitudes towards domestic and imported consumer packaged goods. To this end, a cohort of n=500 Generation Z individuals (between the ages of 18 and 26 years old) were surveyed using a bespoke online questionnaire on the CloudArmy Reactor platform. The subsequent data output was systematically analysed with structural equation modelling (SEM) and metric invariant group difference analyses, which were all carried out on IBM SPSS and Amos version 27. The results of this analysis suggest that the socio-psychological predisposition of patriotism is a highly significant driver of consumer ethnocentric tendencies (CET) in this particular generational cohort. Additionally, the centrality dimension of materialism was observed to exert a converse, negative influence on CET. Willingness to buy, on the other hand, is significantly influenced by both consumer ethnocentrism and implicit attitudes. Most notably, the former relationship was positive, whereas, the latter is negative, suggesting a level of cognitive dissonance as purported by the dual attitude model. Finally, none of the demographic variables were found to moderate the model, with only one path (between financial satisfaction and CET) indicating significant moderation by gender. Importantly, a number of theoretical implications can be gleaned from this study. Most notably, the paper sheds light on many inconsistencies in the extant literature by confirming the nascent conceptualisation of implicit consumer ethnocentrism (ICE). Additionally, it expands on the previously observed moderating variables and highlights the need to examine the effect of materialism’s three sub-dimensions separately. In terms of specific managerial implications, these findings reiterate the value of incorporating patriotic themes into marketing efforts, so as to heighten CET behaviour in South African consumers. As an extension, local practitioners are well advised to use consumer ethnocentrism as a predictable psychographic identifier and driver towards prosocial buying behaviour. In toto, this paper culminates in several other key managerial and theoretical implications which may assist local brand managers guard against the encroaching threat posed by globalisation and heightened competition in the South African FMCG marketplace.
A dissertation submitted in fulfilment of the requirements of the degree of Master of Commerce in Marketing to the Faculty of Commerce, Law and Management, School of Economic and Business Sciences, University of the Witwatersrand, Johannesburg, 2022